Geopoesia Kalunga: identidades territoriais da comunidade Quilombola do Mimoso - Tocantins - Alves, Elizeth da Costa (2020)
Even with the transformations that occurred in the rural space due to modernization, the religious traditions manifested in the festivities and revelries, narratives and stories, godparents relations and webs of social relations, are still preserved by the residents and visitors of Mimoso. This community is located between the municipalities of Arraias and Paranã, in the southeast of the Tocantins state and is part of the quilombos remnants in the north of the Goiás state. They remain and constitute fundamental elements for the history and identity of the community. Identity is a concept that has been addressed by studies in literature and geography, mainly in research whose theoretical and methodological framework starts from cultural paradigms. Thus, for the consolidation of the thesis, we aim to understand how the construction of Kalunga territorial identities takes place in the Quilombola rural community Kalunga do Mimoso, through oral narratives and their narrators of geopoetry. By extension, religious festivals, such as the Folia de Santos Reis and the Folia de Santo Antônio, from 2017 to 2018, became the epicenter of the collection and respective analysis. Reaffirming the importance of oral narratives in the history of humanity is the goal around which our specific objectives are shaped. One of them is to analyze how cultural geography and geopoetry contribute to give recognition to quilombola peoples, how they organize themselves and have constituted their territory. Another one is to map the process of historical and territorial formation of the community and understand its social and cultural relations with the Kalunga community in Goiás. We also discuss the dynamics, structural and symbolic aspects of the Santos Reis and Santo Antônio revelries, regarding the occasion, ritual, memory, performance, and how they influence the construction of vocalities and corporealities. And finally, we analyze the stories and procedures of the narrators in relation to the occasions and the narrative construction. We seek to understand the process of forming identities related to the territory where Kalunga subjects live, in dialogue with the theoretical assumptions of cultural geography and geopoetry. We also adopted some problematic questions for the development of the thesis. These are related to the process of territorial formation of the community and its social and symbolic practices, to the contribution of narratives and parties to the construction of territory and identities in Mimoso, and to the implications that the geographical, political and economic frontier causes among the Kalunga of Tocantins and Goiás. In general, we discussed the choice of the theme and its implications. We present the guiding concepts, the theoretical assumptions, the epistemological paths of cultural geography and popular literature (geopoetry) and the methodological contributions that guide the discussion. We historicize the condition of the black people, the formation of quilombola communities in Brazil and Tocantins and the trajectory of their rights. We bring the historical scenario of this state and its communities. We present IBGE data and historically contextualize the division of the Goiás state, the creation of Tocantins and the separation of a large quilombola community. We also show information about the population, the territorial area, the cultural, economic and geographical activities of this state and the municipality of Arraias and their echoes in the vocation of the narrators of geopoetry. The use of qualitative methodologies such as: oral history, critical analysis of bibliography, participant observation, interviews, discourse analysis, among others, enabled consistent analyzes and reflections on the theme. Throughout the thesis, we present answers to the questions presented initially. We note the importance of the feeling of belonging and social practices for the promotion of Kalunga territorial identities. These are based on the collective participation of the subjects in the process of producing the territory, which transcend the political and administrative perspective, and value the appropriation of space for the reproduction of life, work and the Kalunga culture.